THE ROLE OF PRAGMATICS IN INTERCULTURAL COMMUNICATION - Shoxsanam Marufova (Modern American Journals, 2025)
This article explores the essential role of pragmatics in intercultural communication, focusing on how speakers from different cultural backgrounds interpret meaning beyond the literal content of language. Pragmatic competence enables individuals to navigate culturally embedded norms such as politeness strategies, indirectness, speech acts, and contextual appropriateness. In an increasingly globalized world where cross-cultural encounters are common in education, business, diplomacy, and migration, misunderstandings often arise not from grammar or vocabulary errors, but from pragmatic failures. By analyzing the components of pragmatic competence and its relevance in cross-cultural contexts, the study emphasizes the need for incorporating pragmatic training into language education. The article highlights that a pragmatic perspective not only enhances linguistic understanding but also fosters empathy, reduces stereotyping, and promotes more effective intercultural dialogue.
Keywords: Pragmatics, intercultural communication, speech acts, cross-cultural competence, politeness strategies, pragmatic failure, language education.